1985
DOI: 10.1161/01.cir.72.5.1081
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of pathologic and angiographic findings in a porcine preparation of coronary atherosclerosis.

Abstract: Coronary atherosclerosis was induced in Yorkshire swine by diet-induced hyperlipidemia and balloon intimal abrasion of a coronary artery. Severe stenoses pathologically similar to the lesions of human atherosclerosis were seen after 8 months of the atherogenic regimen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0

Year Published

1988
1988
1998
1998

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(15 citation statements)
references
References 25 publications
0
15
0
Order By: Relevance
“…There is general agreement that coronary angiography in humans underestimates coronary artery disease compared with postmortem specimens. 64 The most credible evaluation of coronary angiography reported to date was a study by Weiner et al 65 in 200-lb pigs in which it was reported that lesion size was underestimated.…”
Section: Future Directions Improved Computerized Image Processingmentioning
confidence: 99%
“…There is general agreement that coronary angiography in humans underestimates coronary artery disease compared with postmortem specimens. 64 The most credible evaluation of coronary angiography reported to date was a study by Weiner et al 65 in 200-lb pigs in which it was reported that lesion size was underestimated.…”
Section: Future Directions Improved Computerized Image Processingmentioning
confidence: 99%
“…Coronary arteries were fixed with pressure perfusion and reangiogramed, and paraffin-sectioned histological specimens were projected, traced, and measured with digital image analysis. Weiner et al 7 found excellent correlation between histological specimens and in vivo images at sites of focal narrowing but also found larger lumens where vessels were normal. This latter finding was attributed to shrinkage during histology processing, despite perfusion fixation at physiological pressures.…”
Section: Calibration Study In Coronary Atherosclerosismentioning
confidence: 94%
“…Selective arteriography has been calibrated against peripheral arterial specimens in intact cadavers under conditions that realistically simulate clinical radiography, 18 but such studies cannot reproduce cardiac motion to test coronary angiography. Except for the study of Weiner et al 7 (discussed in the next section), quantitative coronary angiographic procedures have been calibrated by procedures employing either radiographic test objects, 19 measurements of coronary flow past single constrictions, 20 measurements in excised hearts 21 or arteries, 22 or measurements of total myocardial flow. Win, reader's score used as consensus score; loss, other reader's score used as consensus score; compromise, neither reader's score used as consensus score; win ratio, wins/(losses + compromises).…”
Section: Limitations Of Coronary Imaging Technologymentioning
confidence: 99%
See 1 more Smart Citation
“…1995. In an effort to provide solutions to these problems, several stent et al 1982, Weiner et al 1985, Schwartz &. Holmes 1994.…”
mentioning
confidence: 99%